ACT-05 Present and future of precision-based medicine using cancer genome panels - Natsumeda, Manabu (Neurooncol Adv, 2020)
Background: Two cancer genome panels were approved for use in Japan in 2019, and their application in brain tumors are awaited. We have used CANCERPLEXR and FoundationOne CDx (F1) panels for the realization of precision-based medicine in brain tumors. Patients and methods: From August 2017 to present, we have applied cancer genome panels in 11 times to tumors in 9 patients. We assessed patient data including age, sex, pathology, reason for using the panel and actionability. Results: The range of age of 4 to 69 years (mean 45.2 years), and 5 men and 4 women were studied. Pathological diagnosis was epithelioid glioblastoma (GBM), giant cell GBM, anaplastic ependymoma, anaplastic meningioma, anaplastic large cell type lymphoma, meningeal melanomatosis, enterogeneous carcinoma, choroid plexus carcinoma and pineoblastoma. CANCERPLEXR was performed 7 times and F1 panel 4 times and the reasons included confirmation specific gene mutations such as BRAF V600E and TP53, young (pediatric) age and patient request. In one patient, by analyzing primary and recurrent tissue, we were able to assess genetic hits involved in malignant transformation. Actionable targets were found in 4 (44%) of cases, and action was taken in only 1 epithelioid GBM patient with BRAF V600E mutation, albeit with dramatic response (Kanamaru et al., Acta Neuropathol Commun, 2019). All tumors were microsatellite stable. Conclusions: We were able to understand tumor biology in rare brain tumors using 2 genome panels. We need to increase the percentage of patients actually treated. I will also like to touch briefly on how use genome panels for translational research on brain tumors.